Papua New Guinea : 2011 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Papua New Guinea. (IMF Staff Country Reports; Country Report ;, 2011)
Papua New Guinea showed solid economic growth, supported by greater political stability, fiscal framework, and a healthy banking sector. Executive Directors encouraged the authorities to consider tighter macroeconomic policies in the face of rising inflation pressures and also stressed the need of a tight fiscal policy. They welcomed the Sovereign Wealth Funds (SWF), and considered it important to integrate the use of resources in the SWF into the budget and macroeconomic framework, supported by strong fiscal institutions. Directors observed that Liquefied Natural Gas (LNG) and other resource projects provide an opportunity to raise long-term growth and living standards.